The Effect of Consumer Brand Engagement on Online Brand Experience and Its Consequences on Banking Apps Service - Ria Octavia; Rahmawati Azizah; Shafitranata Shafitranata (Journal of Economics, Business, and Accountancy Ventura, 2023)
Mobile Banking is the most widely used banking service application to meet the needs of online transactions. It is inseparable from the influence of the consumer brand engagement (CBE) concept, which is developing the engagement concept by combining marketing science and psychology with cognitive, affective, and behavioral dimensions. These are likely to generate a lot of positive online brand experiences, brand satisfaction, brand loyalty, and brand trust. This study aims to examine the effect of CBE on brand satisfaction, loyalty, and trust through online brand experience in the context of mobile banking apps. We involved 170 active customers having transacted using m-banking apps through a purposive sampling method and analyzed them using the structural equation model (SEM) approach. We found that CBE positively affects brand satisfaction, loyalty, and trust through online brand experience. This study suggests banks improve the implementation of the CBE concept because it creates a positive online brand experience to produce loyal customers who will benefit the banking business.